Development of AR flashcards to improve students' ESD-based analytical skills in biology - Nabila Azqia; Wiwit Artika; Muhammad Nazar; Afandi Afandi; Muhibbuddin Muhibbuddin (Universitas Negeri Jakarta, 2026)
The development of digital technology has opened new opportunities in education, especially in the creation of interactive learning media. One innovation relevant to 21st-century learning needs is Augmented Reality, which provides a more realistic learning experience by integrating 3D visual elements. In line with modern educational demands, students are expected not only to gain knowledge but also to develop analytical skills for solving real-world problems. This study aims to develop AR-based flashcard media to improve students' ESD-based analytical skills. The study used the R&D method with the ADDIE model, involving 30 10th-grade students at SMA Laboratorium Universitas Syiah Kuala in the 2025/2026 academic year. The research instruments included an expert validation sheet, a System Usability Scale (SUS) questionnaire, a teacher and student response questionnaire, and an analytical skills test. The validation results showed that the media was in the